2004
DOI: 10.1063/1.1829773
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between atomic-layer-deposited HfO2 films using O3 or H2O oxidant and Hf[N(CH3)2]4 precursor

Abstract: The dielectric properties of HfO2 thin films, which were deposited on Si wafers by an atomic layer deposition (ALD) technique at a wafer temperature of 300 °C using a N-containing, tetrakis dimethylamido hafnium precursor (Hf[N(CH3)2]4), were highly improved by adopting O3 as the oxidant during the ALD instead of H2O. The films contained a much smaller carbon impurity concentration and were of more amorphous nature compared to the films grown using H2O as oxidant. Temperature-dependent leakage current analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
72
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 13 publications
0
72
0
Order By: Relevance
“…Hafnium-tetrachloride (HfCl 4 ) and water (H 2 O) have been widely used for depositing HfO 2 using ALD [11][12][13][14]. Recently, there have been reports of using Hf amide type precursors such as Hf(N(CH 3 )(C 2 H 5 )) 4 for HfO 2 or Hf-aluminate to overcome problems such as the excessive particles or residual chlorine obtained when using HfCl 4 precursors [10,14,15,20]. Furthermore, ALD HfO 2 films have been deposited at low temperatures (around 300°C), using a Hf(N(CH 3 )(C 2 H 5 )) 4 precursor and O 3 instead of H 2 O as the oxidant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hafnium-tetrachloride (HfCl 4 ) and water (H 2 O) have been widely used for depositing HfO 2 using ALD [11][12][13][14]. Recently, there have been reports of using Hf amide type precursors such as Hf(N(CH 3 )(C 2 H 5 )) 4 for HfO 2 or Hf-aluminate to overcome problems such as the excessive particles or residual chlorine obtained when using HfCl 4 precursors [10,14,15,20]. Furthermore, ALD HfO 2 films have been deposited at low temperatures (around 300°C), using a Hf(N(CH 3 )(C 2 H 5 )) 4 precursor and O 3 instead of H 2 O as the oxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Of the deposition techniques used for high-k films [10][11][12][13][14][15][16][17][18][19][20], atomic layer deposition (ALD) technology is desirable for precise control of the composition, film thickness, conformality and uniformity. Hafnium-tetrachloride (HfCl 4 ) and water (H 2 O) have been widely used for depositing HfO 2 using ALD [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for some materials it has been reported that improved film properties are obtained when using O 3 or O 2 plasma instead of H 2 O. [2][3][4][5][6][7][8] The potentially more favorable process settings ͑e.g., in terms of substrate temperature and purge times͒ as well as the potentially improved material properties obtained for the O 3 and O 2 plasma based ALD processes have also contributed to an increased interest into ALD by other fields of technology than semiconductor industry. Potential application of ALD films in areas such as microsystems, solar cells, flexible electronics, energy storage, and photonics have recently been reported.…”
Section: Introductionmentioning
confidence: 99%
“…MIM capacitors with Al 2 O 3 dielectric have been investigated using different deposition techniques such as metallorganic chemical vapor deposition, atomic layer deposition (ALD), and pulsed laser deposition [3][4][5]. Among these deposition methods, the ALD technique can provide much superior dielectric properties including low thermal budget and precise control of composition, film thickness, conformality, and uniformity [6,7]. On the other hand, TiN metal electrode is most widely used in electronic devices due to high melting point, metallic conductivity, good chemical stability and ability to against diffusion of metal ions in high-k materials [8].…”
Section: Introductionmentioning
confidence: 99%